Sensitivity and Resolution Capacity of Electrode Configurations - Cyril Chibueze Okpoli (International Journal of Geophysics)
This paper reviews the geological conditions, data density, and acquisition geometry that have direct influence on the sensitivity and resolution capacity of several electrode configurations. The parameters appreciate the effectiveness of automated multichannel system which has evolved several electrode arrays that are cost effective, reduction in survey time, high sensitivity, and resolution capacity in 2D and 3D resistivity tomographies. The arrays are pole-pole, pole-dipole, pole-bipole, dipole-dipole, Wenner, Wenner-, , gradient, midpoint-potential-referred, Schlumberger, square, and Lee-partition arrays. The gradient array and midpoint-potential-referred are well suited for multichannel surveying and gradient array images are comparable to dipole-dipole and pole-dipole. 2D electrical resistivity surveys can produce out-of-plane anomaly of the subsurface which could be misleading in the interpretation of subsurface features. Hence, a 3D interpretation model should give more accurate results, because of the increase in the reliability of inversion images and complete elimination of spurious features. Therefore, the reduction of anomaly effects and damping factor due to signal to noise ratio result in better spatial resolution image, thus enhancing its usage in environmental and engineering research.